Persepsi Guru Terhadap Buku Ajar Tematik SD Inpres 12/79 Lebbae Kecamatan Ajangale Kabupaten Bone - Andi Farida Lestari; Awaluddin Muin; Sitti Jauhar; Nurabidah Idrus (STKIP Andi Matappa Pangkep, 2021)
This research is descriptive qualitative research. This study aims to determine the teacher's perception of thematic textbooks for SD Inpres 12/79 Lebbae, Ajangale District, Bone Regency. The subjects of this study were the teachers of SD Inpres 12/79 Lebbae. The focus of this research is the teacher's perception of thematic textbooks. The data collection instruments used interview guidelines, questionnaires and documentation. Data analysis techniques in research are 1) data reduction 2) Data presentation stage 3) conclusion drawing. The results obtained are the teacher's perception of thematic textbooks, namely that thematic textbooks are very interesting, in terms of color and cover, then in the letters section they use easy-to-read shapes and sizes. The thematic textbook typeface uses Arial font size 12, and the number of pages is 244. In terms of language, the textbook has simple and easy-to-understand words and has motivational sentences. The textbook fulfills the feasibility components such as validity, effectiveness, applicability, and attractiveness as a good textbook, so that this textbook can fill deficiencies and increase the diversity of thematic learning resources, especially at SD Inpres 12/79 Lebbae for use by teachers